Good growth and governance in Africa : rethinking development strategies - Noman, Akbar (Oxford : Oxford University Press, 2012)
This volume examines the history of developmental policy in sub-Saharan Africa and considers how different policy options might generate sustained economic growth and reduce poverty. It documents and interprets policy lessons and considers how to translate them to particular country contexts.
Includes index.
Description based on print version record.
Keywords: Economic development -- Africa, Sub-Saharan.; Africa, Sub-Saharan -- Economic conditions